2007
DOI: 10.1016/j.schres.2007.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Elevated GRIA1 mRNA expression in Layer II/III and V pyramidal cells of the DLPFC in schizophrenia

Abstract: The functional integrity of the dorsolateral prefrontal cortex (DLPFC) is altered in schizophrenia leading to profound deficits in working memory and cognition. Growing evidence indicates that dysregulation of glutamate signaling may be a significant contributor to the pathophysiology mediating these effects; however, the contribution of NMDA and AMPA receptors in the mediation of this deficit remains unclear. The equivocality of data regarding ionotropic glutamate receptor alterations of subunit expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…Our data are consistent with previously reported data indicating a trend for increased NMDAR and AMPAR subunit expression in the DLPFC of a smaller group of MDD subjects. 54 Indeed, it has been suggested that the antidepressant effects of ketamine are dependent on the enhancement of AMPAR activation. 55 Evidence that AMPAR potentiators possess antidepressant-like properties 56 suggests that a relative increase in AMPAR activation produces antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with previously reported data indicating a trend for increased NMDAR and AMPAR subunit expression in the DLPFC of a smaller group of MDD subjects. 54 Indeed, it has been suggested that the antidepressant effects of ketamine are dependent on the enhancement of AMPAR activation. 55 Evidence that AMPAR potentiators possess antidepressant-like properties 56 suggests that a relative increase in AMPAR activation produces antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] Moreover, 2 other genes whose THCmediated deregulation during adolescence persisted at 75 PND, Gria1 and Reln, have also been found to be modified in postmortem studies per formed in the cortex of patients with schizophrenia. [44][45][46][47] Thus, the 2 main THCinduced epigenetic events, the early (0-24 h) H3K9me3 upregulation followed by a delayed (24-48 h) in crease of H3 acetylation, dramatically change the physiologic expression of the analyzed genes. These genes may play a cru cial role in the correct developmental trajectory of the adolescent brain, thus their aberrant expression could affect the shaping of adult brain organization.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GluA1 has also been implicated in the pathophysiology of schizophrenia [9, 21, 24, 25]. Decreased expression levels of GluA1 have been found in the brain of some schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%